PROSES PEMULIHAN KORBAN PENYALAHGUNAAN NAPZA (NARKOTIKA, PSIKOTROPIKA DAN ZAT ADIKTIF) DI BALAI REHABILITAS SOSIAL KORBAN PENYALAHGUNAAN NAPZA “INSYAF” MEDAN SUMATERA UTARA. - Suharniyati Suharniyati; Mahzaniar Mahzaniar (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the role of BRSKPN "Insyaf" in Empowering Drug Abuse Victims in Medan, North Sumatra in 2021. This study uses a descriptive method using a qualitative approach. The discovery of the sample used in this study was through data collection and interviews. Informants in this study were Rehabilitation Center staff and clients who were users and social workers. The results showed that the role of Social Rehabilitation for Drug Abuse Victims "Insyaf" in providing services was very good, it can be seen from the programs that have been given to clients so that clients are able to be more independent and can develop talents and interests. The Social Rehabilitation Center for Drug Abuse Victims provides training that is able to hone the skills of clients so that when clients leave the "Insyaf" Rehabilitation Center, they can support themselves and be able to compete with the general public.